2012
DOI: 10.1002/mds.25157
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter imaging is associated with long‐term outcomes in Parkinson's disease

Abstract: Dopamine (DA) transporter (DAT) imaging has been studied as a diagnostic tool for degenerative parkinsonism. Our aim was to measure the prognostic value of imaging for motor and nonmotor outcomes in Parkinson’s disease (PD). We prospectively evaluated a Parkinson’s cohort after enrollment in a de novo clinical trial with a battery of motor (UPDRS), cognitive (Montreal Cognitive Assessment), and behavioral measures. DAT imaging with [123I][β]-CIT and single-photon emission computerized tomography (SPECT) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 27 publications
8
89
2
Order By: Relevance
“…In the general population, an association between DAT binding and cognitive function was demonstrated in 12 individuals without PD, 35 and in a cohort of 491 PD patients, de novo at baseline, lower baseline striatal DAT binding was associated with global cognitive decline over a 22-month period. 36 Conversely, cognitive reductions in prodromal PD may be partially mediated by early extrastriatal disease pathology or nondopaminergic systems. This is supported by animal data; in a mouse model of PD, cognitive dysfunction (abnormalities in spatial learning and novel object recognition) was noted preceding motor abnormalities and before loss of dopaminergic neurons was expected.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, an association between DAT binding and cognitive function was demonstrated in 12 individuals without PD, 35 and in a cohort of 491 PD patients, de novo at baseline, lower baseline striatal DAT binding was associated with global cognitive decline over a 22-month period. 36 Conversely, cognitive reductions in prodromal PD may be partially mediated by early extrastriatal disease pathology or nondopaminergic systems. This is supported by animal data; in a mouse model of PD, cognitive dysfunction (abnormalities in spatial learning and novel object recognition) was noted preceding motor abnormalities and before loss of dopaminergic neurons was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that DA at high concentrations may participate in neurodegenerative processes, such as in Parkinson's disease (Ahlskog 2007;Ravina et al 2012). Although cocaine is able to inhibit the reuptake of DA, noradrenaline and serotonin, its powerful effect is believed to ensue from its actions on the dopamine transporter (DAT) in neuron terminals, causing an increase of the concentration and of the intensity of action of DA at the postsynaptic receptors ( Fig.…”
Section: Dopamine Toxicity Caused By Cocaine Addictionmentioning
confidence: 98%
“…to aid in the diagnosis of Parkinson disease and other Parkinsonian syndromes such as Lewy body dementia and progressive supranuclear palsy (1,2). DAT imaging is special among clinical nuclear medicine scans in that the already small caudate and putamen, with average volumes of 3.4 and 4.3 cm 3 , respectively (3), are presented in multiple thin axial cuts.…”
Section: Dopami Ne Transporter (Dat) Imaging Is a Valuable Toolmentioning
confidence: 99%